Statistical Analysis of Factors Influencing Women's Career Progression in the Hospitality Industry - Choudhary, Satyanarayan (Darul Yasin Al Sys, 2025)
The hotel industry, characterized by its labor-intensive nature and dynamic operational environment, has witnessed increasing female participation in recent decades; however, women’s progression into leadership and executive positions remains disproportionately limited. This study investigates the factors influencing women's career advancement within the hotel sector, focusing on both structural barriers and enabling mechanisms. Utilizing a quantitative research design, data were collected in 2024 through a structured online questionnaire distributed via email and social media platforms to a purposive sample of hospitality professionals across multiple organizational levels. Key variables examined include organizational culture, work-life balance, mentorship access, gender bias, and professional development opportunities. Data analysis revealed significant constraints impeding women's career growth, notably systemic gender biases, limited access to strategic networking opportunities, and insufficient flexible work arrangements. In contrast, critical enablers identified include the presence of equitable workplace policies, access to mentorship and sponsorship programs, and the availability of structured leadership development initiatives. The study’s findings underscore the complex interplay of institutional and cultural dynamics that shape women's career trajectories in the hospitality industry. It highlights the urgent need for targeted policy reforms, inclusive human resource practices, and sustained organizational commitment to diversity and equity. These results offer actionable insights for hospitality leaders and policymakers aiming to foster more inclusive career progression frameworks and strengthen gender equity in leadership within the sector.